A new flying capacitor multilevel converter topology with reduction of power electronic components - Rokan Ali Ahmed; Enas Dawood Hassan; Adham Hadi Saleh (Institute of Advanced Engineering and Science, 2023)
High power capacity and reliability are characteristics of multilevel inverters. The using a collection of DC sources can produce a terminal voltage that is very close to sinusoidal. The power quality can be improved by adding more levels, but this makes the control system more complicated and expensive. The number of power components in a multilevel inverter has been studied for decades. So, research needs to be done on multilevel inverter configurations to find ways to add levels with fewer power switches than with traditional topologies and those that have already been proposed. In this research, a new power-efficient arrangement of a flying-capacitor inverter is introduced. In order to illustrate the suggested topology, a seven-level multilevel inverter is constructed and demonstrated in a simplified form. Fewer power components, including power switches, capacitors, and gate driver circuits, are required in this topology than in other topologies described in the recent literature, which is one of its main advantages. The improvement mentioned above can be seen in the way this topology works, which is shown by the characteristics of the circuit. MATLAB/Simulink R2021a is used to simulate and verify the circuit to ensure the proposed topology is correct.